Breathing lung transplantation with the Organ Care System (OCS) Lung: lessons learned and future implications - Lightle, William; Daoud, Daoud; Loor, Gabriel (Journal of Thoracic Disease, 2019)
Ex vivo lung perfusion (EVLP) represents a potentially important advancement in the preservation of donor lungs prior to transplantation. Portable EVLP or “Breathing Lung Transplantation” with the Organ Care System (OCS) Lung combines the fundamental components of EVLP with portability, thus reducing the total ischemic burden. The Food and Drug Administration (FDA) approved OCS for perfusion of standard donor lungs prior to transplant in 2018. The current review discusses the available literature on the clinical outcomes of OCS Lung as well as translational data.